1975
DOI: 10.1111/j.1471-0528.1975.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Feto‐maternal Haemorrhage Following Successful and Unsuccessful Attempts at External Cephalic Version

Abstract: In the present study, 6 out of 100 patients who had an attempted or actual external cephalic version (ECV) showed significant feto-maternal haemorrhage, the amount being greatest in patients with "failed" external versions. Thus ECV may be a source of rhesus iso-immunization in a rhesus negative mother with a rhesus positive fetus and should not be performed unless the father is rhesus negative. If, however, an ECV has been attempted, fetal cell counts should then be made and rhesus immunoprophylaxis administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 8 publications
0
13
0
3
Order By: Relevance
“…COHEN [1] and LUBIN [5] have suggested that such hemorrhages are a normal finding due to the trauma of labour. Several authors have stressed that their incidence is increased by external cephalic version [2,6,8,13], traumatic amniocentesis [9,16] and cesarian section [11]. As illustrated by the present case, spontaneous cephalic version may possibly account for another cause of feto-maternal transfusion resulting in severe neonatal anemia.…”
Section: Discussionmentioning
confidence: 79%
“…COHEN [1] and LUBIN [5] have suggested that such hemorrhages are a normal finding due to the trauma of labour. Several authors have stressed that their incidence is increased by external cephalic version [2,6,8,13], traumatic amniocentesis [9,16] and cesarian section [11]. As illustrated by the present case, spontaneous cephalic version may possibly account for another cause of feto-maternal transfusion resulting in severe neonatal anemia.…”
Section: Discussionmentioning
confidence: 79%
“…The largest bleed in their study was 117 cells/10,000 maternal cells, which corresponds to 6.5 ml of fetal red cells. Although Marcus et al [8] found an increase in the amount of FMH in cases with failed ECV, Tau et al [10] found no such association. Placental position has been related to success rates [3,6] and a posterior placenta is considered more favourable.…”
Section: Discussionmentioning
confidence: 95%
“…The largest volume of FMH was 6.0 ml in the study by Marcus et al [8] and there were no adverse outcomes. The largest amount of FMH was found in those with failed ECV.…”
Section: Discussionmentioning
confidence: 99%
“…Initial cephalic presentation [11], marked oligohydramnios [3], encephalocele [1], and a nonreactive, suspicious initial electronic monitoring tracing [1] led to candidate rejection (figure 2). In 53/85 cases (62.5%) ECV was successful.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that our patients frequently traveled long distances for the procedure and with uncertainties of patient follow-up, we routinely administered immune globulin to all Rh negative patients with an ECV attempt [9,11,12]. In series in which KLEINHAUER-BETKE studies have been performed, 4 -28% of version patients have shown evidence of measurable fetomaternal bleeding [8,16].…”
Section: Discussionmentioning
confidence: 99%